Quality improvement in virtual classroom - Bajracharya, Sumana; Shrestha, Ashis; Jnawali, Pramod (Journal of Patan Academy of Health Sciences, 2019)
Introductions: Online teaching method has shown to be equally effective as the traditional teaching method. An online teaching method, the virtual classroom (VCR) was developed for undergraduate medical students of Patan Academy of Health Sciences (PAHS). This study aims to present the outcome of complete audit cycle of VCR for quality improvement of the program.Methods: Feedbacks were collected from final year medical students who are posted in four different rural sites of PAHS. A validated google feedback form was used to collect the feedbacks from individual students after every VCR sessions. Students from 2017 were group one and students from 2018 were group two. Feedbacks were recorded in Likert scale of five. Ratings were done for quality of video, sound and power supply. Plan, do, study, and act (PDSA) cycle was used for quality improvement process. The necessary changes were done after analysis of data from group A. Same process was repeated for group B.Results: Fifty-six feedbacks were collected in first cycle. The complete PDSA audit cycle showed improvement in quality of VCR, with mean score on video of 3.0 and 4.1, audio 3.1 and 4.03, internet 3.6 and 4.03, power supply 4.0 and 3.98 in first cycle group A vs second cycle group B.Conclusions: Improvement was achieved by running quality feedback cycle and quality improvement cycle should be continued to maintain the quality achieved with this process.